A review for discovering hepatoprotective herbal drugs with least side effects on kidney - Majid Shirani; Roya Raeisi; Saeid Heidari-Soureshjani; Majid Asadi-Samani; Tahra Luther (Society of Diabetic Nephropathy Prevention, 2017)
The liver is a vital organ which plays a major role in the metabolism and excretion of xenobiotics from the body, and liver disease is a worldwide health problem. The currently available synthetic drugs to treat liver disorders cause further damage to the liver and kidney so it is imperative to find new drugs with least side effects. There are a number of treatment combinations which are derived from medicinal plants and commonly administered as tonic for the liver. In this review, we have introduced most important medicinal plants that are used in liver disorders and have least side effects on kidney. In this regards, we have focused on their active constituents, effects and trial studies, mechanisms of action, pharmacokinetic characteristics, dosages, and toxicity. Amaranthus spinosus L., Glycyrrhiza glabra, Cichorium inthybus L., Phyllanthus species (amarus, niruri, emblica), Picrorhiza kurroa, and Silybum marianum have been extensively administered for the treatment of liver disorders. The introduced medicinal plants can be used for production of new drugs via antioxidant-related properties, hepatoprotective activities and least side effects on kidney for the prevention and treatment of liver disorders.